Investigation of biomass combustion and conceptual design of a fluidized-bed - ,, Muhtadin; ,, Erdiwansyah; ,, Muhammad Faisal; ,, Mahyudin; ,, Hamdani; ,, Khairil; Mel, Maizirwan (Penerbit Akademia Baru, 2020)
This study investigates the combustion process of empty fruit bunches (EFB) and palm kernel shells (PKS) in a bubbly fluidized-bed combustion chamber. The biomass combustion simulation process uses a kinetic model consisting of chemical kinetic and hydrodynamic flow. This modelling is based on the two-phase theory in the fluidized bed. Where both phases in the bed are assumed that there are a mass and energy transfer between them. These phases include the emulsion phase and the bubble phase which contains solid particles. The constant temperatures throughout the reactor are assumed in this modelling. This study also investigates the parametric and effects of various parameters carried out. The experimental research shows that there is a change in bed diameter and has a negligible effect on combustion performance. The results of biomass combustion experiments with a fluidized-bed design have promising and satisfying results compared to several experimental studies in the literature. In addition, the increase in reactor temperature and a bed height of combustion efficiency also increased. However, the moisture of the biomass and the speed of the fuel entering can affect various for combustion efficiencies. Suitable operating conditions can produce maximum overall efficiency.